Fluoride release of six restorative materials in water and pH-cycling solutions - Rosa Maria Viana de Bragança Garcez; Marília Afonso Rabelo Buzalaf; Paulo Amarante de Araújo (University of São Paulo, 2007)
The fluoride release of restorative materials in deionized water has been the subject of many studies, but the behavior of these materials under conditions of acid challenge that simulates the oral cavity, needs to be further explored. Therefore, the aim of this study was to evaluate the fluoride release of restorative materials in two storage protocols: deionized water and pH-cycling system (demineralizing solution-pH 4.3 and remineralizing solution-pH 7.0) for 15 days. Eight disks of each material (Vitremer™-positive control, Dyract AP, Ariston pHc, Definite®, Tetric®Ceram and Z100-negative control) were prepared (11.0 mm x 1.5 mm) and suspended individually in 4.0 mL of each solution, which were daily changed. Daily fluoride release was analyzed with an ion specific electrode (Orion 9609) by the direct method or after HMDS-facilitated diffusion, following 1, 7 and 15 days. The values obtained were converted into µgF/mm² and the data analyzed by ANOVA and Tukey's test (p< 0.05). The results showed that all materials released more fluoride in the pH-cycling system, except for Ariston pHc which maintained a constant release during the experiment. The highest fluoride release was presented by the positive control, Vitremer™ in pH-cycling and by Ariston pHc, in deionized water. The negative control Z100 and the resins Definite® and Tetric®Ceram did not present statistically significant differences.